2018
DOI: 10.1007/s00425-018-2959-x
|View full text |Cite
|
Sign up to set email alerts
|

Current advances in gibberellic acid (GA3) production, patented technologies and potential applications

Abstract: Gibberellic acid is a plant growth hormone that promotes cell expansion and division. Studies have aimed at optimizing and reducing production costs, which could make its application economically viable for different cultivars. Gibberellins consist of a large family of plant growth hormones discovered in the 1930s, which are synthesized via the terpenes route from the geranylgeranyl diphosphate and feature a basic structure formed by an ent-gibberellane tetracyclic skeleton. Among them, only four have biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
83
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 83 publications
0
83
1
7
Order By: Relevance
“…Exogenous application of plant growth phytohormones has been regarded as an effective way to alleviate negative effects of salinity. Among these, gibberellins have been recorded to be a promoter for plant growth under salinity conditions [19][20][21][22][23] which can relieve seed dormancy, promote plant gene expression, increase the synthesis of hydrolase in plants, repair damaged cell membranes and improve seed vitality. Previous studies have shown that the use of exogenous gibberellic acid (GA 3 ) can promote seed germination, improve the salt tolerance of seeds, and alleviate the inhibition of salt on seedling growth [22,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous application of plant growth phytohormones has been regarded as an effective way to alleviate negative effects of salinity. Among these, gibberellins have been recorded to be a promoter for plant growth under salinity conditions [19][20][21][22][23] which can relieve seed dormancy, promote plant gene expression, increase the synthesis of hydrolase in plants, repair damaged cell membranes and improve seed vitality. Previous studies have shown that the use of exogenous gibberellic acid (GA 3 ) can promote seed germination, improve the salt tolerance of seeds, and alleviate the inhibition of salt on seedling growth [22,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The study was done before and following application of a phytohormone, gibberellic acid (GA3), after an hour. GA3 is considered to be an important phytohormone responsible for green revolution and is widely used either on its own or with other growth hormones such as auxin or cytokinin to enhance the growth (Camara et al, 2018;Yamaguchi, 2008). Thus, techniques that require monitoring the action of plant hormones within an intact tissue providing high temporal and spatial resolutions are needed.…”
Section: Introductionmentioning
confidence: 99%
“…GA 3 is considered to be an important phytohormone responsible for green revolution and is widely used either on its own or with other growth hormones such as auxin or cytokinin to enhance the growth (Camara et al, 2018;Yamaguchi, 2008). Thus, techniques that require monitoring the action of plant hormones within an intact tissue providing high temporal and spatial resolutions are needed.…”
Section: Introductionmentioning
confidence: 99%